2021
DOI: 10.1021/acs.nanolett.1c01440
|View full text |Cite
|
Sign up to set email alerts
|

Optical Signatures of Dirac Electrodynamics for hBN-Passivated Silicene on Au(111)

Abstract: The allotropic affinity for bulk silicon and unique electronic and optical properties make silicene a promising candidate for future high-performance devices compatible with mature complementary metal−oxide−semiconductor technology. However, silicene's outstanding properties are not preserved on its most prominent growth templates, due to strong substrate interactions and hybridization effects. In this letter, we report the optical properties of silicene epitaxially grown on Au(111). A novel in situ passivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…47,48 Nevertheless, it has been shown that the Dirac features are preserved even under a high deformation of the silicene layer. 47,49 As mentioned earlier, the structural modification of silicene could have been triggered by the weak interaction with the fluoride layer. It has been observed that, through the intercalation of F − ions in a CaSi 2 crystal, silicene bilayers are obtained.…”
Section: ■ Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…47,48 Nevertheless, it has been shown that the Dirac features are preserved even under a high deformation of the silicene layer. 47,49 As mentioned earlier, the structural modification of silicene could have been triggered by the weak interaction with the fluoride layer. It has been observed that, through the intercalation of F − ions in a CaSi 2 crystal, silicene bilayers are obtained.…”
Section: ■ Discussionmentioning
confidence: 91%
“…We note that this structural change does not depend on the amount of deposited CaF 2 but just on the interaction with the capping material. It can be expected that such a structural modification will also have an impact on the electronic properties of the 2D layer. , Nevertheless, it has been shown that the Dirac features are preserved even under a high deformation of the silicene layer. , …”
Section: Discussionmentioning
confidence: 99%
“…According to the method described in Ref. 20 and the compatibility of silicene with h-BN encapsulation 27 , we present the method shown in Fig. 9 in order to fabricate the proposed OMOSFET.…”
Section: Fabrication Processmentioning
confidence: 99%
“…Generally, in addition to Al 2 O 3 , h-BN is also used between silicene and oxide layers to maintain the structure, high carrier mobility 26 , and optical properties of silicene 27 . The h-BN layer as a buffer is important in the fabrication of devices based on intrinsic silicene 24 .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Among 2D-Xenes, silicene attracts particular attention because of its unique properties and technological potential. 8 Similar to graphene, silicene demonstrates signatures of Dirac electrodynamics; 9 its applications range from field-effect transistors 10 to Li-ion batteries. 11 It could be a wonder material but there is a catch – silicene and other 2D-Xenes exhibit high chemical reactivity making them difficult to handle.…”
Section: Introductionmentioning
confidence: 99%